Identification of novel genetic variations affecting osteoarthritis patients. Issue 1 (October 2016) - Gari, Mamdooh; AlKaff, Mohammed; Alsehli, Haneen; Dallol, Ashraf; Gari, Abdullah; Abu-Elmagd, Muhammad; Kadam, Roaa; Abuzinadah, Mohammed; Gari, Mazin; Abuzenadah, Adel; Gauthaman, Kalamegam; Alkhatabi, Heba; et al.
Abstract Background Osteoarthritis (OA) is a progressive joint disease characterized by gradual degradation of extracellular matrix (ECM) components in the cartilage and bone. The ECM of cartilage is a highly specified structure that is mainly composed of type II collagen and provides tensile strength to the tissue via aggrecan and proteoglycans. However, changes in the ECM composition and structure can lead to loss of collagen type II and network integrity. Several risk factors have been correlated with OA including age, genetic predisposition, hereditary factors, obesity, mechanical injuries, and joint trauma. Certain genetic association studies have identified several genes associated with OA using genome-wide association studies (GWASs). Results We identified several novel genetic variants affecting genes that function in several candidate causative pathways including immune responses, inflammatory and cartilage degradation such as SELP, SPN, and COL6A6. Conclusions The approach of whole-exome sequencing can be a promising method to identify genetic mutations that can influence the OA disease.